ANALISIS STRATEGI PENINGKATAN KUALITAS PRODUK DALAM MEWUJUDKAN KEPUASAN KONSUMEN PADA FAMILY SNACK CIBUBUR KOTA JAKARTA TIMUR - Ramadini, Nosalia Rahmi; Kurniawaty, Erlita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze product quality improvement strategies in achieving customer satisfaction at Family Snack Cibubur, East Jakarta. The background of this research is based on the increasingly competitive snack food industry, requiring businesses to enhance product quality and provide optimal service to maintain customer loyalty. Product quality and customer satisfaction are key factors in improving competitiveness and ensuring business sustainability. This study employs a qualitative descriptive method with data collection techniques including observation, in-depth interviews, and documentation. The informants consist of the business owner, employees in administration, display, packaging, and cashier sections, as well as customers. Data analysis techniques include data reduction, data presentation, and conclusion drawing supported by SWOT analysis. The results indicate that the product quality improvement strategies implemented by Family Snack include selecting high-quality raw materials, maintaining consistent taste, using attractive and safe packaging, ensuring product cleanliness, and improving friendly and responsive service. Based on the SWOT analysis, the business is positioned in Quadrant I (progressive strategy), indicating strong internal strengths that can effectively utilize external opportunities. Product quality improvements oriented toward customer needs have been proven to increase customer trust, satisfaction, and repurchase intention. Therefore, the combination of product quality and service becomes a key factor in creating customer loyalty and supporting business sustainability in a dynamic market environment.